A Randomized, Controlled Trial of Mirror Therapy for Upper Extremity Phantom Limb Pain in Male Amputees - Finn, Sacha B.; Perry, Briana N.; Clasing, Jay E.; Walters, Lisa S.; Jarzombek, Sandra L.; Curran, Sean; Rouhanian, Minoo; Keszler, Mary S.; Hussey-Andersen, Lindsay K.; Weeks, Sharon R.; Pasquina, Paul F.; Tsao, Jack W. (Frontiers in Neurology, 2017)
Objective Phantom limb pain (PLP) is prevalent in patients post-amputation and is difficult to treat. We assessed the efficacy of mirror therapy in relieving PLP in unilateral, upper extremity male amputees. Methods Fifteen participants from Walter Reed and Brooke Army Medical Centers were randomly assigned to one of two groups: mirror therapy (n = 9) or control (n = 6, covered mirror or mental visualization therapy). Participants were asked to perform 15 min of their assigned therapy daily for 5 days/week for 4 weeks. The primary outcome was pain as measured using a 100-mm Visual Analog Scale. Results Subjects in the mirror therapy group had a significant decrease in pain scores, from a mean of 44.1 (SD = 17.0) to 27.5 (SD = 17.2) mm (p = 0.002). In addition, there was a significant decrease in daily time experiencing pain, from a mean of 1,022 (SD = 673) to 448 (SD = 565) minutes (p = 0.003). By contrast, the control group had neither diminished pain (p = 0.65) nor decreased overall time experiencing pain (p = 0.49). A pain decrement response seen by the 10th treatment session was predictive of final efficacy. Conclusion These results confirm that mirror therapy is an effective therapy for PLP in unilateral, upper extremity male amputees, reducing both severity and duration of daily episodes. Registration NCT0030144 ClinicalTrials.gov.